Ultrasound Strain Relaxation Time Ratio: A Quantitative Marker for the Assessment of Cortical Inflammation/Edema in Renal Allografts - Gao, J.; Hentel, K.; Kazam, J.; Min, R. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Purpose: To evaluate the ability of ultrasound strain relaxation time ratio to assess cortical inflammation/edema in renal allografts.Materials and Methods: We prospectively assessed renal allograft cortical inflammation/edema in 16 renal transplants using ultrasound elasticity imaging and correlated the findings with kidney biopsy. Strain relaxation times in the renal cortex and reference soft tissue were produced by free-hand compression with the ultrasound transducer and estimated with 2 D speckle tracking. Compression was performed in 3-second compression-relaxation cycles (push for 1 second, constant pressure for 1 second, and release for 1 second). We propose a strain relaxation time ratio (time of cortical strain to return to zero/time of the reference strain return to zero) to assess the relationship of compression-induced time-dependent strain relaxation in the cortex and reference tissue. 16 patients were divided into a group with ≤ 25 % (n = 8) and a group with > 26 % (n = 8) cortical inflammation/edema based on the Banff score. A t-test was used to examine the difference in the strain relaxation time ratio between the two groups. The diagnostic accuracy, inter-rater reliability, and reproducibility of this technique in discriminating between the groups were tested.Results: The strain relaxation time ratio of cortex/reference tissue was significantly higher in patients with > 26 % than in patients with ≤ 25 % cortical inflammation/edema (1.15 ± 0.10 vs. 0.91 ± 0.08, P = 0.0002). The strain relaxation time ratio has high reliability (Pearson correlation coefficient, R² = 0.93), reproducibility (intraclass correlation coefficient = 0.98, P = 0.000), and accuracy (area under curve = 1) in determining > 26 % renal cortical inflammation/edema.Conclusion: The strain relaxation time ratio of cortex/reference tissue can be used as a quantitative marker for the assessment of cortical inflammation/edema in renal allografts.
Keywords: ultrasound; abdomen; renal allograft; ultrasound elasticity imaging; strain relaxation time